Activation of the Peroxisome Proliferator-Activated Receptors (PPAR-α/γ) and the Fatty Acid Metabolizing Enzyme Protein CPT1A by Camel Milk Treatment Counteracts the High-Fat Diet-Induced Nonalcoholic Fatty Liver Disease - Haifa M. AlNafea; Aida A. Korish (PPAR Research)
Camel milk (CM) has a unique composition rich in antioxidants, trace elements, immunoglobulins, insulin, and insulin-like proteins. Treatment by CM demonstrated protective effects against nonalcoholic fatty liver disease (NAFLD) induced by a high-fat cholesterol-rich diet (HFD-C) in rats. CM dampened the steatosis, inflammation, and ballooning degeneration of the hepatocytes. It also counteracted hyperlipidemia, insulin resistance (IR), glucose intolerance, and oxidative stress. The commencement of NAFLD triggered the peroxisome proliferator-activated receptor-α (PPAR-α), carnitine palmitoyl-transferase-1 (CPT1A), and fatty acid-binding protein-1 (FABP1) and decreased the PPAR-γ expression in the tissues of the animals on HFD-C. This was associated with increased levels of the inflammatory cytokines IL-6 and TNF-α and leptin and declined levels of the anti-inflammatory adiponectin. Camel milk treatment to the NAFLD animals remarkably upregulated PPARs (α, γ) and the downstream enzyme CPT1A in the metabolically active tissues involved in cellular uptake and beta-oxidation of fatty acids. The enhanced lipid metabolism in the CM-treated animals was linked with decreased expression of FABP1 and suppression of IL-6, TNF-α, and leptin release with augmented adiponectin production. The protective effects of CM against the histological and biochemical features of NAFLD are at least in part related to the activation of the hepatic and extrahepatic PPARs (α, γ) with consequent activation of the downstream enzymes involved in fat metabolism. Camel milk treatment carries a promising therapeutic potential to NAFLD through stimulating PPARs actions on fat metabolism and glucose homeostasis. This can protect against hepatic steatosis, IR, and diabetes mellitus in high-risk obese patients.